2021
DOI: 10.3390/su13115803
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Stress Response of Nurse Students in an Objective Structured Clinical Examination (OSCE)

Abstract: The aim of the present research was to analyze the autonomic stress response of nursing students in a nursing Objective Structured Clinical Evaluation (OSCE). We analyzed, in 41 s-year nursing degree students (20.1 ± 2.3 years), modifications in heart rate variability (HRV) to monitor the autonomic stress response before, during and after the 18 different scenarios of a complete OSCE. Heart rate mean response of nurse students was consistent with an anticipatory anxiety response at the beginning of the OSCE, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…During the whole clinical practice, where the habituation process was absent, a high sustained sympathetic activity was registered [ 7 ]. The same case scenario was found in nursing students during the performance of an ECOE [ 5 ].…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…During the whole clinical practice, where the habituation process was absent, a high sustained sympathetic activity was registered [ 7 ]. The same case scenario was found in nursing students during the performance of an ECOE [ 5 ].…”
Section: Discussionmentioning
confidence: 59%
“…We also analysed the stress and grade perception of students pre- and post-clinical case; we also measured the difficulty perception at the end of the clinical practice. Stress was measured on a subjective scale from 0 (no stress) to 100 (maximum stress), difficulty perception was measured from 0 (no difficulty) to 100 (maximum difficulty), and academic performance was measured on a 0 to 10 scale [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research [11] has shown as uncertain and unpredictable environments produce a large anxiogenic response in students that could negatively affect their ability to cope with the acquisition of learning process [11][12][13]. Evaluation context as final degree defence, clinical stays or practical evaluations produce a large stress response of students due to this uncertainty and unpredictability [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%